Activity-dependent reduction of dopamine D2 receptors during a postnatal critical period of plasticity in rat striatum is not affected by prenatal haloperidol treatment - Soiza Reilly, Mariano (2011)
Motor activity induced in the Circling Training test (CT) during a postnatal (PN) critical period of plasticity (PN30-37) produces a long-lasting decrease in the number of binding sites and mRNA expression levels of the dopamine D2 receptor (D2R) in rat striatum. Prenatal exposure to the antipsychotic haloperidol also decreases postnatal levels of the striatal D2R in the offspring. We examined whether such fetal exposure to haloperidol could affect the activity-dependent reduction of the D2R system during the critical period. Half of the male offspring exposed to either haloperidol (2.5. mg/kg/day), i.p.) or saline during gestational days 5-18 were subjected to the CT during the critical period, while the remaining represented CT control animals. The adult number of binding sites and mRNA expression levels of the striatal D2R at PN90 were not changed by prenatal haloperidol treatment alone. On the other hand, only pups subjected to the CT during the critical period showed decreases in both studied parameters, regardless the prenatal treatment. These findings indicated that the postnatal reduction of the striatal D2R binding induced prenatally by haloperidol does not affect long-lasting activity-dependent plastic changes on the same receptor system elicited by motor activity in an ontogenetic critical period of plasticity in rat striatum.